Sudden unexpected death in epilepsy (SUDEP): don't ask, don't tell?. Issue 2 (17th January 2006) - Morton, B; Richardson, A; Duncan, S
Abstract : Background: The National Institute for Clinical Excellence in the UK has issued guidelines stating all individuals with epilepsy be given information about sudden unexpected death in epilepsy (SUDEP). Methods: We conducted a survey of current practice among UK neurologists, using a questionnaire sent to all practising neurologists in the UK listed on the Association of British Neurologists database, asking under what circumstances they told patients about SUDEP. Results: Of the validated respondents, 5% discussed SUDEP with all patients, 26% with a majority, 61% with a few, and 7.5% with none. The commonest reasons for SUDEP to be discussed were the patient asking about it and the neurologist counselling people with known risk factors for SUDEP. Conclusions: The variation we found, although not necessarily in tune with the guidelines, reflects the variation in patients' need for knowledge about their condition.